Single-Channel Seismic Images from the Hudson Canyon and Western North Atlantic Ocean acquired during the R/V Robert D. Conrad expedition RC2101 (1977) (IEDA: Marine-Geo Digital Library, 2004)
This data set was acquired with the LDEO Single-Channel Seismic system during R/V Robert D. Conrad expedition RC2101 conducted in 1977 (Chief Scientist: Dr. Charles Windisch). These data files are of JPEG format and include Single-Channel Reflection Seismic images that have not been processed after acquisition. Funding was provided by NSF grant: N00014-75-C-0210.